Novel approaches to the diagnosis of Mycobacterium bovis infection in African buffaloes (Syncerus caffer) - Bernitz, Netanya (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.